The Effect of Convenience and Security on Satisfaction with Customer Interest as Mediator - Shadiba Maharani, Eureka; Sekarsari, Meidiati; Zhafiraah, Nazma Riska (SAN Scientific, 2024)
This research was conducted to determine the influence of perceived convenience and security on customer interest in using BNI mobile banking with customer satisfaction as a mediator. The sampling technique used is nonprobability sampling (purposive sampling) with a customer population of the BNI Kelapa Gading branch with a sample size of 100 respondents. This research uses an associative approach using the Path Analysis method and is calculated. The results of this research show that perceived convenience has a positive effect on interest in using mobile banking, security has a positive effect on interest in using mobile banking, perception of convenience has no effect on customer satisfaction, security has no effect on customer satisfaction, and interest in using mobile banking has a positive effect on customer satisfaction and interest in using mobile banking do not mediate perceptions of convenience and security on customer satisfaction. The managerial implication of this research is improving user experience. This implication can be through streamlining processes and a better understanding of user needs. Improved system security to show that perceived security influences customer satisfaction and increased communication and education through marketing campaigns that focus on security features and convenience in mobile banking applications.